2019
DOI: 10.1136/bmjopen-2018-028052
|View full text |Cite
|
Sign up to set email alerts
|

How do nursing students experience the clinical learning environment and respond to their experiences? A qualitative study

Abstract: IntroductionOn entry into the clinical environment, nursing students are confronted with many challenges. It is a common problem throughout the world, including Iran. Although many studies have been conducted on the problems of nursing students in the clinical environment, limited information is available on nursing students’ experiences of the clinical learning environment and the way they respond to these experiences. Identifying nursing students’ experiences is essential to develop interventions to reduce c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 30 publications
0
90
0
9
Order By: Relevance
“…Several authors reported that showing respect to students, supporting their learning needs and good communication are the key qualities of an effective clinical educator. [12][13][14] Delany and Golding suggested the use of "making thinking visible approach" as a pedagogical approach to develop the clinical reasoning. They believed that the clinical teachers using this approach are forced to make their thinking visible so they start to reflect about their clinical reasoning teaching and it facilitates them to articulate their own reasoning process by scaffolding it to the students, who can access and use it in their practice.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors reported that showing respect to students, supporting their learning needs and good communication are the key qualities of an effective clinical educator. [12][13][14] Delany and Golding suggested the use of "making thinking visible approach" as a pedagogical approach to develop the clinical reasoning. They believed that the clinical teachers using this approach are forced to make their thinking visible so they start to reflect about their clinical reasoning teaching and it facilitates them to articulate their own reasoning process by scaffolding it to the students, who can access and use it in their practice.…”
Section: Discussionmentioning
confidence: 99%
“…The professional performance, regardless of the work context, requires the worker to have previous knowledge of its function, of work environment and of the population who will receive support. 11 Data analysis showed how the trainings provided to these professionals have occurred.…”
Section: Preparation and Professional Training In Federal Prison Unitsmentioning
confidence: 99%
“…The institutions, when planning their training proposals, should consider the clarification and elucidation of norms, routines, manuals of procedures in order to offer security to the worker, help in its decision-making, in addition to grant uniformity to the discourse and transparency in a company's objectives. 11 Still, regarding the training of professionals to work in their respective prison units, one can notice that the institution offer few courses addressed to the worker's practice and enhancement. In order to enhance and develop knowledge aligned with the work routine, these professionals request courses and trainings from the responsible board; however, these resources, which depend on the institution approval, are sometimes denied.…”
Section: There Is No Standardization There Are No Manuals Of Procedumentioning
confidence: 99%
“…Nursing education aims to equip students with the knowledge, skills, attitudes and self-esteem they will need while performing nursing profession (1)(2)(3)(4) . Nursing students acquire professional qualifications through education offered in school and clinical settings (5)(6)(7)(8) . Internalization of the powers, roles and responsibilities of nursing by students through receiving a qualified education (2,6,9) is significant for professionalization in nursing (1,6,7) .…”
Section: Introductionmentioning
confidence: 99%
“…Nursing students acquire professional qualifications through education offered in school and clinical settings (5)(6)(7)(8) . Internalization of the powers, roles and responsibilities of nursing by students through receiving a qualified education (2,6,9) is significant for professionalization in nursing (1,6,7) . Clinical training is an essential part of professional nursing education since it ensures the transformation of the knowledge gained through theoretical education into skills, equips students with empathic approach and critical decision-making and effective communication skills, and allows for observing and applying nursing care interventions (3,4,7,(10)(11)(12)(13) .…”
Section: Introductionmentioning
confidence: 99%